The effectiveness of important healthcare reforms in the Jizzakh region during the years of independence (using the example of protecting motherhood and childhood) - Jurayev , Anvar (The Lingua Spectrum, 2025)
The issue of maternal and child health occupies a central position in the healthcare system reforms of Uzbekistan. Uzbekistan is one of the countries in the Central Asian region with a high birth rate, and children constitute a significant part of the population. This requires special attention to protecting maternal health in order to ensure the birth of a healthy generation. In addition, strengthening the material and technical base in this area is also one of the most important issues.